Utilizing Social Network in Teaching Writing by Developing Genre-Based Approach: EFL Students’ Attitudes & Perceptions - Rija Dwiono; Nur Arifah Drajati (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
Social Network has changed beyond the boundaries from it was first perceived. Nowadays, it is not only used for recreation but also it means in teaching. However, addiction and privacy risk for students in using a social network are inevitable. Therefore, proper implementation is required to gain the maximum benefits of the social network. This study is aimed to examine the role of the social network by developing the Genre-based approach in teaching writing measured from students’ attitudes and perceptions in EFL setting. Social network Facebook was focused to use regardless of other applications while the researcher served as a moderator. A survey was used to measure factors affected by developing the Genre-based approach in the social network in teaching writing. By employing the qualitative and quantitative method, the finding shows that social network is successfully implemented in teaching writing and it supported students’ needs by developing the Genre-based approach to improve their pre-writing activity.</p.